Protocol and Feasibility-Randomized Trial of Telehealth Delivery for a Multicomponent Upper Extremity Intervention in Infants With Asymmetric Cerebral Palsy. (22nd September 2020) - Pietruszewski, Lindsay; Burkhardt, Stephanie; Yoder, Paul J.; Heathcock, Jill; Lewandowski, Dennis J.; Maitre, Nathalie L.
Background: Past work showed that an in-person, therapist-guided, parent-implemented multicomponent intervention increased the motor functioning of the more affected upper extremity (UE) in infants with asymmetric cerebral palsy. The authors document treatment fidelity and provide initial testing of telehealth intervention delivery in a new subject sample. Methods: The authors adapted the intervention manual used in the previous trial for telehealth. Infants (6-24 months) were randomly assigned to intervention (n = 7) or waitlist (n = 6). The intervention prescribed soft-constraint wear on the less affected UE for 6 hours, 5 d/wk, and exercises. After an initial in-person training session, three 15- to 45-minute telehealth sessions were performed. Results: Median weekly constraint wear was 21 hours (interquartile range = 10.3-29.7); average parent-treatment fidelity was 95.7% (SD 11.2). A significant large (Cohen d = 0.92) between-group differences occurred on fine motor functioning of more affected UEs. Conclusion: The telehealth intervention was feasible and potentially effective, but a larger trial is needed to evaluate efficacy.